What happens to cavitated primary teeth over time? A 3.5‐year prospective cohort study in China. (11th April 2013) - Hu, Xuan; Chen, Xi; Fan, Mingwen; Mulder, Jan; Frencken, Jo E.
Abstract : Objectives: Data showed that among 5‐year‐old Chinese, 96.7% of cavitated primary teeth were left untreated. The study aimed to report on the course of cavitated primary teeth within the Chinese health‐care system over a period of 3.5 years. Methods: Selection of high caries risk children for inclusion in a sealant comparison study was based on the presence of cavitated dentine lesions in their primary teeth. At the 6‐month sealant evaluation point many of these cavitated dentine lesions had not been treated. This necessitated monitoring these cavitated teeth 6‐monthly for those exfoliated, restored, with a cavity left open, having caused toothache (symptom) and having (or having had) an abscess or fistulae (symptom). Care‐seeking instruction was given at every evaluation point.anova and t ‐test were used in analysing the data. Results: A total of 1012 cavitated primary teeth in 305 children (7.6 to 9.3 years old), were followed for 3.5 years. A total of 92.9% of cavitated primary teeth were left open, while 7.1% were restored at some stage during the observation period; 98.5% of restored teeth and 95.5% of cavitated teeth left open exfoliated and 93.9% of restored teeth and 81.5% of cavitated primary teeth left open exfoliated without any symptoms. Having (or having had) toothache was the symptom most frequently related to exfoliated restored teeth and to exfoliated cavitated teeth left open. Restored primary teeth survived statistically significantly longer than cavitated primary teeth left open: 1.99 ± 0.07 years and 1.68 ± 0.03 years, respectively. Conclusion: The large majority of cavitated primary teeth in this child population exfoliated without symptoms.